About Mafia and Work. Reading a Sicilian CGIL’s document (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
The text introduces the document delivered by the Sicilian CGIL Secretariat to the Anti-Mafia Parliamentary Commission in October 1963. It traces the season of the popular struggles against the feud and for agrarian reform, emphasising the role of the left-wing forces and the violent reaction of the landowners and the Mafia.
Keywords: Sicily; Mafia; Trade Union; Peasants; Mobilisations